Matilda - Dahl, Roald; Blake, Quentin (Puffin London, 2013)
Matilda longs for her parents to be good and loving and understanding. But they are none of these things. They are perfectly horrid to her. Matilda invents a game of punishing them each time they treat her badly and she soon discovers she has supernatural powers. She applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security